Fatigue Crack Growth Behaviour of Sandwiched Metal Panel of Aluminium and Mild Steel under Constant Amplitude Loading - Isahak, A. H.; Abdullah, M. F.; Faidzi, M. K.; Ali, A.; Mubasyir, M. M. (International Journal of Integrated Engineering, 2020)
This study concerned about the sandwiched metal panel on the fatigue crack growth of mild steel and aluminium. The fatigue crack growth consists of 3 layer of metal sheet or panel that bonded together using adhesive of epoxy resin by hand lay-up technique. The 3 layers are consisting of 2 face metal sheets and 1 metal sheet as a core for the sandwiched; sandwiched of aluminium with mild steel panel (SAMSP) and sandwiched of mild steel panel (SMSP). The specimen was cut using Electrical Discharge Machine Wire Cut (EDM-wire cut) to get tensile test specimen based on American Standard Testing Method (ASTM) E8 before tested with speed rate of 3mm/min using Universal Testing Machine Instron 5569A (UTM). The stress strain curve was plotted in order to analyse the yield strength, Ultimate Tensile Strength (UTS) and the Young’s Modulus of the sandwiched. UTS value is used for the fatigue test in the maximum stress applied between 0.50%, 0.60%, 0.70%, 0.80% and 0.90% of UTS. The fatigue test was conducted under ASTM E647 compact tension C(T) standard using Instron 8801 Fatigue Machine with constant frequency of 20Hz and subjected to 1 million cyclic loading to reach failure. The crack growth behaviour of the specimen were discover that indicate the fatigue life, (a-N), fatigue crack growth and failure of the structure by the initial notch. The sandwiched of mild steel panel (SMSP) is compared with the sandwiched of aluminium with mild steel panel (SAMSP) to observe the crack growth behaviour and mechanical properties of the specimen in this study. It can be determined that SAMSP has two times better crack growth behaviour that improve the structure properties compare to the SMSP.